Systematic Literature Review (SLR) on Financial Performance in State-Owned Enterprises (SOEs) in Indonesia - Eko Darmawan Suwandi; Akhmad Syarifudin (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study aims to systematically review the development of financial performance research on Indonesian State-Owned Enterprises (SOEs) during the 2015–2024 period. SOEs play a strategic role in Indonesia’s economy; however, recurring issues such as inefficiency, weak governance, financial distress, and the impact of the Covid-19 pandemic have raised concerns regarding their financial sustainability. This research employs a Systematic Literature Review (SLR) approach following the framework of Kitchenham and Charter. Articles were collected from Google Scholar using the search string “Financial Performance of SOEs,” with inclusion criteria limited to peer-reviewed journal articles published between 2015 and 2024 and focusing on financial performance analysis. A total of selected studies were analyzed to identify dominant themes, measurement methods, determinants, and findings related to SOEs’ financial performance. The results indicate that while several SOEs demonstrate healthy financial performance based on profitability, liquidity, and solvency ratios, a significant number continue to experience poor performance due to weak management practices, high debt levels, inefficiency, and governance issues. The findings also reveal mixed evidence regarding the impact of privatization on financial performance, with some studies reporting improvements and others indicating no significant effect. Furthermore, the Covid-19 pandemic substantially worsened the financial condition of many SOEs, particularly in capital-intensive sectors. This study contributes by synthesizing empirical evidence on SOE financial performance and provides insights for policymakers and SOE management to strengthen governance, efficiency, and financial resilience.